ANTARA WAKAF DAN RIBA - Hidayah, Ma'rifatul; RIDWAN, MURTADHO (ZISWAF, 2016)
God destroyed the usury and fertilize the charity. This is a fragment the meaning of paragraph 276 surat al-Baqarah. In this verse Allah promised to destroy usury and fertilize the charity. Among the types of charity who have the quest reward is waqf. Therefore it can be a solution wafaf destruction of usury on this earth. This article aims to examine the role of endowments in eradicating usury that exist in society. The study, which used is a literature review with given examples of cases in the community. The results of the study concluded that if the waqf property is well managed and in line with sharia, the waqf property can be used to destroy usury. Examples are waqf property used to build traditional market for the provision of modern scales, to assist the capital of the merchants, to create exchange programs dime before the feast, and for other programs. For success, the necessary role in empowering Nazhir waqf property. In addition, the Innovation program created by Nazhir determine the success of the role of waqf property in eliminating usury.